Risk of Developing Hepatocellular Carcinoma following Depressive Disorder Based on the Expression Level of Oatp2a1 and Oatp2b1. (29th July 2019) - Chen, Yan; Zhang, Jiongshan; Liu, Mengting; Zou, Zengcheng; Wang, Fenglin; Hu, Hao; Sun, Baoguo; Zhang, Shijun
Abstract : Background . Accumulating evidence from prospective epidemiological studies has showed that depression disorder (DD) is a risk factor for cancer. The aim of this study is to explore the association of DD and the overall occurrence risk of hepatocellular carcinoma (HCC) and the mechanism. Methods . In this study, 60 mice were randomly divided into four groups: Control group, DD group, HCC group, HCC-DD group. Mice received a chronic dose of reserpine to establish depression model, followed by Diethylnitrosamine and Carbon tetrachloride administration to establish HCC models. Behavioral depression was assessed by sucrose preference test (SPT) and the expression of Serotonin 1A (5-HT1A) receptor in the hippocampal. The expression of Oatp2a1 and Oatp2b1 in the digestive system tissues was detected by PCR and western blotting. Results . Reserpine-administrated mice had a reducing sucrose preference at Day 14 compared with blank mice (P<0.05). The expression of 5-HT1A receptor in the hippocampal was decreased in DD mice compared with blank mice. The survival analysis indicated that the HCC mice with DD have poorer survival rate compared with the HCC mice. Compared with HCC mice, the expression of Oatp2a1 and Oatp2b1 was lower in liver and stomach tissue and higher in hepatic carcinoma and colon tissue of HCC-DD mice (P<0.05), and the expression of Oatp2a1 was higher in the spleen tissue of HCC-DD mice while the expression of Oatp2b1 was lower (P<0.05). However, no difference was found in the expression of Oatp2a1 and Oatp2b1 in the small intestine tissue between HCC group and HCC-DD group. Conclusions . DD was the adverse factors for the overall occurrence risk of HCC. Mechanistically, be the downregulation of Oatp2a1 and Oatp2b1 in liver tissue induced by DD might be involved.